2017
DOI: 10.1007/s00128-017-2172-9
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Temperature and the Microcystin MC-LR on the Feeding Behavior of the Rotifer Brachionus calyciflorus

Abstract: The aim of this study was to investigate the responses in filtration and grazing rates of five rotifer strains of the species Brachionus calyciflorus under different temperatures and MC-LR concentrations. The results showed that strain identity, MC-LR concentration, temperature, and the interactions of these factors significantly affected both response variables, with the exception of the interaction of strain and MC-LR on the grazing rates. At low MC-LR concentrations and for the control group, the filtration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Such temperature-mediated toxicity could be responsible for the 50% decline observed in the survival of I. elegans exposed to high concentration of the crude extract at 25 °C in our study. Here, our finding supports the hypothesis on the combined effects of temperature and crude extract and corroborates earlier studies that demonstrated their combined effects on freshwater species (Kim et al 2014 ; Lamb et al 2019 ; Xiang et al 2017 ). Hence, the present study suggests that warming may co-occur with a much broad range of cyanobacterial metabolites following bloom senescence leading to impaired survival and feeding among important species (Paerl and Huisman 2008 ; Walls et al 2018 ).…”
Section: Discussionsupporting
confidence: 93%
“…Such temperature-mediated toxicity could be responsible for the 50% decline observed in the survival of I. elegans exposed to high concentration of the crude extract at 25 °C in our study. Here, our finding supports the hypothesis on the combined effects of temperature and crude extract and corroborates earlier studies that demonstrated their combined effects on freshwater species (Kim et al 2014 ; Lamb et al 2019 ; Xiang et al 2017 ). Hence, the present study suggests that warming may co-occur with a much broad range of cyanobacterial metabolites following bloom senescence leading to impaired survival and feeding among important species (Paerl and Huisman 2008 ; Walls et al 2018 ).…”
Section: Discussionsupporting
confidence: 93%
“…The effects of high CPZ concentrations on rotifer population dynamics could be explained by the following factors. To begin, the swimming speed of the rotifer determines its water filtration rate and feeding rate [ 76 ], and rotifers move significantly slower in highly concentrated CPZ solutions, where food deprivation may be among the main factors influencing population growth. Secondly, the activities of several enzymes, including lipase, amylase and acetylcholinesterase, as well as the expression of cytochrome P450s genes, have been linked to changes in rotifer populations [ 67 ], but the effect of CPZ on rotifer survival and reproduction has yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…There was a significant reduction in the small-sized particles (0.5-2.5 lm) in our culture ( Figure 5) indicating the probability that P. similis fed on these particles. Rotifers are filter feeders (Xiang et al, 2017) and feed on particles less than their body size (Hino & Hirano, 1984;Ogata, Tokue, Yoshikawa, Hagiwara, & Kurokura, 2011;Starkweather & Gilbert, 1977). They also show particle size-dependent feeding (Vadstein, Øie, & Olsen, 1993).…”
Section: Discussionmentioning
confidence: 99%